Pengembangan E-Modul Berbasis Model RME (Realistic Mathematics Education) Menggunakan Rumah Pangeran Duayu untuk Meningkatkan Kemampuan Pemecahan Masalah Pada Materi Keliling dan Luas Bangun Datar Kelas IV SD - Sadela Nurhayani; Agus Susanta; Irwan Koto (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to determine the feasibility of the material, language, design, teacher and student responses, as well as the effectiveness of the product resulting from the development of an RME-based e-module using the "Prince Duayu" house to improve problem solving skills for grade IV SD. This research is an ADDIE Research and Development (R&D) model. The subjects were students of SDN 4 Bengkulu Selatan, The instruments used were interview guides, questionnaires, and problem-solving ability tests in the form of essay questions through the pretest and posttest.. The data analysis technique in this study was validation analysis using Aiken's V and Interrater Reliability, teacher and student responses, as well as quantitative analysis using the T-test. The results of validating material, language, design, as well as teacher and student responses to e-modules are very appropriate and well used in learning so that students are happy and interested in learning mathematics in flat shape material. The results of the effectiveness of the e-module are effective in solving students' mathematical problems. Judging from the results of the significance value, which is 0.01, it is smaller than α = 0.05. Based on the gain-score test from the use of the e-module, it gives a moderate gain score of 47%. Thus, the mathematical problem-solving abilities of students who use e-modules based on the RME model using the "Prince Duayu" house are higher than students who only use textbooks from school so that they are declared effective.